Analisis Hukum terhadap Pelaku Aborsi berdasarkan Pasal 75 Ayat (2) Jo Pasal 194 Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan: Analisis Putusan Nomor:482/Pid.Sus/2021/Pn Ckr - Mochamad Haris Candra Purnama; Zaenal Arifin (Advokasi Hukum & Demokrasi (AHD), 2025)
Abortion has always been a hot topic, especially regarding criminal abortion provocatus which is increasingly found in modern society and industries that are experiencing globalization. What is the criminal responsibility of abortion perpetrators based on Article 75 paragraph (2) Jo Article 194 of Law No. 17 of 2023 concerning Health. To find out the legal responsibility What is the criminal responsibility of abortion perpetrators based on Article 75 paragraph (2) Jo Article 194 of Law No. 17 of 2023 concerning Health. There are also medical records that are useful in determining something related to a doctor's actions. Medical records have a very important function and role in the health sector, including in law enforcement efforts, especially proving malpractice cases in the medical field. The police should be more careful in handling abortion cases and perhaps this can be done by approaching teenagers by providing counseling on the dangers of abortion, the negative impacts of promiscuity, and the police should be able to work together with doctors or midwives who know about abortion and if there are teenagers who come to doctors or midwives to have abortions, they should be reported to the police.